16th Century Sundanese Royal Trade - Sariat Arifia; Randy Van Zichem; Arsyad Arsyad; Wahyu Bagja Sulfemi; Daniel Zuchron (Ridwan Institute, 2023)
This article aims to clarify the existence of the Sundanese scientifically in an authoritative form, namely a kingdom that has a clear scope of territory, power and authority so that the Sundanese have the ability to carry out trade, especially in the 16th century and apart from colonial historiographical architecture, that the Sundanese only did cultural activities, mystical, marginalized, have no trade records. The research method used is the historical method which includes five stages of work, namely heuristics, field visits, criticism, interpretation, and historiography. Grounded Theory is also used as a research methodology approach. Research in the field is used as an effort to reconstruct historical architecture that is clean from the influence of stories of pitting against one another carried out by colonialism. The results of this study indicate that even though the Sundanese are known to have a strong culture, the strong Sundanese trading side was